Призначення та функції керівника в процесі управління будівельною організацією - Зінченко, М. М.; Омельяненко, О. П.; Гончаров, В. В. (Ways to Improve Construction Efficiency, 2014)
The article deals content categories "head", "Management", "leader", "management function". Analyzed the function of the head associated with human relationships. We consider the practical role of head of a construction company in the management process.